The freshwater ribbon-worm Prostoma graecense (Hoplonemertea: Monostilifera) in South America (Argentina) - Tamburi, Nicolas Eduardo (2006)
The morphological species Prostoma graecense (Böhmig, 1892) is reported for the first time fromArgentina and South America. Some diagnostic characters, such as the ciliated epithelium of thenon-rhynchodaeal oesophagus and the backward extension of the cephalic glands up to the braincommisure, were confirmed for the Argentine material; the rhynchodaeal longitudinal muscleswere present, but did not form a thick layer as expected from some previous descriptions. AddingSouth America to its distribution range supports the hypothesis that this morphotype Prostomagraecense actuallyhas a cosmopolitan distribution.